2018
DOI: 10.1002/jhet.3427
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Biological Evaluation of 2‐(4‐Aminophenyl)benzothiazole Analogues as Antiproliferative Agents

Abstract: A series of 28 novel 2‐(4‐aminophenyl)benzothiazole analogues have been synthesized and characterized using various analytical techniques like 1H NMR, 13C NMR, electrospray ionization mass spectrometry, and IR and bioevaluated for their antiproliferative activity over a group of three human cancer cell lines, namely, lung cancer (A549), cervical cancer (HeLa), and breast cancer (MDA‐MB‐231), using sulforhodamine B assay method. Few synthesized molecules (5a, 5c, 5d, 5f, 7b, and 7j) displayed effective growth i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 34 publications
2
7
0
Order By: Relevance
“…Aniline 1ac was synthesized by minor modifications of a reported procedure. 43 Into a pressure tube equipped with a magnetic stirrer were added 4-aminobenzoic acid (1.37 g, 10.0 mmol, 1 equiv) and polyphosphoric acid (4 g). The reaction mixture was gently heated to obtain a homogeneous mixture, before adding 2-aminophenol (1.04 mL, 10.0 mmol, 1 equiv).…”
Section: ■ Experimental Sectionsupporting
confidence: 85%
See 2 more Smart Citations
“…Aniline 1ac was synthesized by minor modifications of a reported procedure. 43 Into a pressure tube equipped with a magnetic stirrer were added 4-aminobenzoic acid (1.37 g, 10.0 mmol, 1 equiv) and polyphosphoric acid (4 g). The reaction mixture was gently heated to obtain a homogeneous mixture, before adding 2-aminophenol (1.04 mL, 10.0 mmol, 1 equiv).…”
Section: ■ Experimental Sectionsupporting
confidence: 85%
“…The reaction mixture was then diluted with EtOAc (25 mL), transferred to a round-bottom flask, and the solvent was evaporated in vacuo. The crude mixture was purified by flash column chromatography on silica gel from hexane 100% to 90:10 hexane/EtOAc obtaining the TEMPO-adduct as a white amorphous solid (26.7 mg, 0.096 mmol, 32%): TLC (hexane/EtOAc 90:10) R f 0.65; 1 (43), 149 (20), 125 (100), 97 (40).…”
Section: ■ Experimental Sectionsupporting
confidence: 84%
See 1 more Smart Citation
“…The synthesis of benzo[d]thiazolyl-phenyl-chloroacetamide was achieved by treating aminophenyl-benzothiazole with haloacetyl chloride in the presence of triethylamine, and further reacting with piperazines-based compounds at 100 • C produced the end products. Benzo[d]thiazolyl-propynyl-aniline was synthesized by treating aminophenylbenzothiazole with propargyl bromide [84].…”
Section: Synthesis Of Anticancer Agentsmentioning
confidence: 99%
“…For example, In 2019, Diao et al [18] have reported compound V, which demonstrated strong anticancer activity against HCT116, HeLa, MCF-7, PC-3, and MDA-MB-231 cancer cell lines with IC 50 0.70, 10.91, 0.45, 1.80, and 0.92 µM, respectively. Narva et al [19] in 2018 have reported a novel series of 2-(4-aminophenyl) benzothiazole analogs and found 4-(benzo[d]thiazol-2-yl)-N-{ [1-(3-methoxyphenyl)-1H-1,2,3-triazol-4-yl]methyl}aniline (VI) most active against HeLa cancer cell line; it showed excellent inhibitory activity with an IC 50 value of 0.98 µM. Lee et al [20] have reported derivatives of 2-aminobenzothiazole with potent anticancer activity.…”
mentioning
confidence: 99%